Utilization of dental care service and associated factors among pre-school children in northwest China over the past decade - Xiao Hu; Xiaoyu Fan; Jiangang Tian; Bin Zhang; Ruizhe Huang (BMC, 2023)
Abstract Objective The purpose of this study was to analyze the factors influencing the utilization of oral health care among 5 years old children. Methods We conducted two observational cross-sectional studies. The studies were conducted in 2005 and 2015 and included 5-year-old children who underwent dental examination by trained dentists and the caregivers of the children were requested to answer the questionnaire. Multi-level stratified sampling method was used. Chi-square tests were used to analyze the utilization of dental care and other socio-economic variables. Logistic regression models were employed to explore the primary factors influencing the use of dental care among pre-school children. Results In 2005, a total of 399 and in 2015, 492 child-caregiver pairs were included. The majority of the caregivers in both surveys were females, comprising 68.2% and 74.8% of the caregivers in 2005 and 2015, respectively. 75.2% and 87.0% (p < 0.05) of the respondents had an education level of lesser than 9 years. The prevalence of caries was higher in 2015 (63.2%) (p < 0.05) than in 2005 (53.4%). In 2005 and 2015, the utilization of dental care services was 20.8% and 20.0%, respectively. A statistically significant association was observed between caries and dental care use in 5-year-olds over the past decade. After adjusting for confounders, dental service usage among children in urban areas was 1.62 times higher than that of rural areas in 2005 (95% CI 0.069-0.571), and the self-assessment of caregivers regarding their child's oral health significantly improved oral health use in 2015. Conclusion The utilization of dental care services over the past decade is insufficient among pre-school children in northwest China. Hence, with the decreasing gap about economic and health service resources, policymakers should place greater emphasis on raising awareness among caregivers about the oral health status of their children.